How to Strengthen Accounting Transparency For? Small and Medium - Sized Enterprises - Olga SHVETSOVA; Yun Beom CHOI (Communications of International Proceedings, 2020)
This study seeks to find ways to reduce accounting transparency among unlisted small and medium-sized enterprises (SMEs) and strengthen them. Korean accounting transparency increases internationality at the mid- to low-income level every year after year. Transparency in accounting will affect the information environment and capital costs of companies, ultimately serving as an important factor in Korea discount, and furthermore, it is an important issue directly related to Korea's international credibility. Research is needed to solve these problems, but the preceding study mainly developed the accounting transparency index or provided policy guidelines to improve it on the premise that the accounting transparency of our country is low. In order to enhance the overall level of accounting transparency in Korea, it is necessary to grasp the actual state of accounting transparency of not only listed companies but also unlisted small and medium-sized enterprises and devise measures to improve them. Therefore, the purpose of this study is to identify the factors that impede the accounting transparency of small and medium-sized enterprises in Korea and to suggest measures to enhance their accounting transparency.
Keywords: Accounting transparency; SME; South Korea; strengthen methods and recommendations.